Mesenchymal Stromal Cells from the Epidermis and Dermis of Psoriasis Patients: Morphology, Immunophenotype, Differentiation Patterns, and Regulation of T Cell Proliferation - M. E. Castro-Manrreza; L. Bonifaz; O. Castro-Escamilla; A. Monroy-García; A. Cortés-Morales; E. Hernández-Estévez; J. Hernández-Cristino; H. Mayani; J. J. Montesinos (Stem Cells International)
Psoriasis is a skin disease characterized by hyperproliferation of keratinocytes and chronic inflammation. Mesenchymal stem/stromal cells (MSCs) exhibit an immunoregulatory function that can be altered in the skin of these patients. However, to date, the presence and functional capacity of MSCs in the dermis and epidermis of patients with psoriasis have not been fully established. In the present study, we evaluated the presence of MSCs in the skin of patients by obtaining adherent cells from the dermis and epidermis of lesional and nonlesional areas and characterizing them in a comparative manner with corresponding cells obtained from the dermis (HD-MSCs) and epidermis (HE-MSCs) of healthy donors. We determined whether the adherent cells had immunophenotypic profiles and differentiation potentials that were characteristic of MSCs. In addition, we analyzed their immunosuppression function by evaluating their capacity to decrease T cell proliferation. Our results indicate the presence of MSCs in the dermis and epidermis of healthy donors and patients with psoriasis; adherent cells from all skin sources exhibited MSC characteristics, such as expression of CD73, CD90, and CD105 markers and a lack of hematopoietic and endothelial marker expression. However, the cell populations obtained showed differences in differentiation potential toward adipogenic, osteogenic, and chondrogenic lineages. In addition, we observed a low MSC obtention frequency in nonlesional epidermal samples (NLE-MSCs), which also showed alterations in morphology and proliferation rate. Interestingly, MSCs from both the nonlesional dermis (NLD-MSCs) and lesional dermis (LD-MSCs) showed higher HLA class I antigen (HLA-I) expression than HD-MSCs. Moreover, NLD-MSCs showed a low T cell proliferation suppression capacity. In summary, this study demonstrates the presence of MSCs in the epidermis and dermis of patients with psoriasis and suggests that such cells may favor the inflammatory process and thus psoriatic lesion development through high HLA-I expression and low immunosuppression capacity.